1997
DOI: 10.1021/la970578v
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Electrochemical Characterization of Langmuir−Blodgett Films of (2,3,9,10,16,17,23,24-Octakis((2-benzyloxy)ethoxy)phthalocyaninato)copper and Its Metal-free Analogue

Abstract: Spectroscopic, electrochemical and spectroelectrochemical, and scanning probe microscopic characterization of thin films of (2,3,9,10,16,17,23,ethoxy)phthalocyaninato)copper, and its dihydrogen analogue, in contact with aqueous electrolytes is described. These materials form highly ordered Langmuir-Blodgett (LB) thin films, where the phthalocyanine (Pc) rings orient with the plane of the ring nearly perpendicular to the compression direction on the LB trough. The resultant thin films show remarkable mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 43 publications
3
66
0
Order By: Relevance
“…The densely crosslinked nature of TPD-Si 2 films is evident in the relatively large separation of oxidative and reductive peaks (200 mV), suggesting kinetically hindered oxidation/reduction processes with retarded counterion mobility. [22] That TPD-Si 2 film coverage on ITO is conformal and largely pinhole-free is supported by studies using a previously described ferrocene probe technique. [23] The lack of significant current flow near the formal potential for ferrocene oxidation at a TPD-Si 2 -coated ITO working electrode indicates suppression of ferrocene oxidation, consistent with largely pinhole-free surface coverage.…”
mentioning
confidence: 87%
“…The densely crosslinked nature of TPD-Si 2 films is evident in the relatively large separation of oxidative and reductive peaks (200 mV), suggesting kinetically hindered oxidation/reduction processes with retarded counterion mobility. [22] That TPD-Si 2 film coverage on ITO is conformal and largely pinhole-free is supported by studies using a previously described ferrocene probe technique. [23] The lack of significant current flow near the formal potential for ferrocene oxidation at a TPD-Si 2 -coated ITO working electrode indicates suppression of ferrocene oxidation, consistent with largely pinhole-free surface coverage.…”
mentioning
confidence: 87%
“…6, curve 1) contains two Q bands in the visible region char acteristic of solutions of phthalocyanine ligands. [25][26][27][28] A decrease in the solution concentration by two orders of magnitude (curve 2) neither changes the spectrum shape, nor shifts the characteristic bands. The green color of the solution also indicates that the ligand exists in the mono (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the effort of many scientists working on enhancement of the electric properties of phthalocya nine films and the efficiency of their production has been directed toward synthesis of octa substituted amphiphilic derivatives [331][332][333][334][335][336][337][338]. It was shown that such compounds can form true monolayers consisting of stacking aggregates and existing upon compression up to pressures of no more than 10-15 mN/m.…”
Section: Electric Conductivity and Magnetic Properties Of Lbfmentioning
confidence: 99%